Clinical case of diagnosis and treatment of insulinoma - Natalia A. Nikitina; Artyom V. Snitsar; Marina V. Kuandykova; Konstantin A. Pokrovsky; Sergey A. Yerin; Vyacheslav A. Shibitov; Natalia V. Brevnova; Nina A. Petunina (LLC "MEDIAFORMAT", 2024)
Insulinoma is a rare neuroendocrine pancreatic tumor that typically produces excessive amout of hormone insulin. The main clinical manifestations of insulinoma are episodes of hypoglycemia. The low prevalence of the disease, the complexity of clinical and laboratory diagnosis, as well as the difficulty of topical diagnosis, low awareness physicians of related specialties, often cause untimely diagnosis of the disease, which worsens patients life-quality and prognosis. This article presents a clinical case of diagnosis and treatment of insulinoma in a non-specialized hospital. The article describes the methods of laboratory and topical diagnostics, as well as treatment tactics of patients with this disease.